Maurice Merleau - Ponty: Body and Psychopathology: MAURICE MERLEAU – PONTY: CORPO E PSICOPATOLOGIA. - Valverde Felipe, Jonathan Levi (2025)
The paper discusses the contributions that science has made to the understanding of manthroughout history and highlights its methodological limitations that prevent it fromaddressing exclusively human aspects. That aspect is the body, understood by science as aset of organs that respond to stimuli; however, this is not exhausted in the purely objective,but transcends it. In this sense, phenomenological postulates allow us to understand theexperience of the body in a different way. To this end, the proposals of the French philosopherMaurice Merleau-Ponty are analyzed. Finally, we reflect on the contributions of his thoughtto psychopathology.